PERSEPSI ANGGOTA MASYARAKAT SEKITAR TENTANG PERILAKU MENYIMPANG (MESUM) YANG TERJADI DI WARUNG JAGUNG BAKAR KELURAHAN SIANTAN HULU PONTIANAK - Yudha Widaya, Sandy (Jurnal Pendidikan Sosiologi dan Humaniora, 2018)
This study aims to determine the perception of Neighborhood Community Members around the Roasted Corn Shop on nasty behavior that occurs in the Roasted Corn Shop Siantan Hulu. The general problem of this study is how the perception of the Neighborhood Community Members around the Roasted Corn Shop on nasty behavior that occurs in there. The form of the study that is used is a qualitative method of data collection through descriptive method. The data collecting techniques are observation, interview and documentation study, while the data collection tools are the observation guide, interview guide and documentation. The research shows that people around there, have a different perception of the nasty behavior which occurs in that shop.